Reducing the recycle flue gas rate of an oxy-fuel utility power boiler. (15th January 2015) - Gao, Haining; Runstedtler, Allan; Majeski, Adrian; Yandon, Robert; Zanganeh, Kourosh; Shafeen, Ahmed
Highlights: Studied concepts to manage temperature at reduced recycle flue gas rate. Acceptable temperature could be achieved with 55% flue gas recycling. Used additional heat transfer surfaces, reduced inlet gas temperature. Also used novel firing strategies to manage furnace temperature. The heat transfer through the radiant areas is increased at reduced flue gas rate. The heat flux on the furnace walls is higher at reduced recycle flue gas rate. Abstract: Oxy-fuel combustion is a technology for capturing CO2 from coal fired power plants. One drawback of this technology is the need for a large quantity of recycled flue gas (RFG) to avoid excessively high temperatures inside the furnace. Instead of only using RFG to manage flue gas temperature, this paper presents and evaluates the concept of using additional heat transfer surfaces in the boiler furnace, reduced incoming gas temperature and combustion control technologies to manage the flue gas temperature in an oxy-fuel boiler with reduced RFG rate. A 1000 MWe ultra-supercritical coal fired utility power boiler was modified using these concepts and studied using a computational fluid dynamics (CFD) model. The combustion, temperature, and heat transfer characteristics of the boiler were compared for three cases: (i) standard air combustion mode, (ii) conventional oxy-fuel combustion mode recycling 72% of the exhaust flue gas, and (iii) the novel oxy-fuel boiler concept recycling 55% of the exhaust flue gas. It is shown by the CFD results that the modified 1000 MWe boiler could achieve an acceptable temperature level in its furnace while recycling 55% of total exhaust flue gas in spite of an increase in predicted temperature level. The predicted heat transfer through the radiant heat transfer areas of the modified boiler, including the furnace walls and platen super heater is significantly increased. Some heat transfer surfaces traditionally arranged in the convective heat transfer sections would need to be arranged inside furnace as radiant heat transfer surfaces for operation at oxy-fuel combustion mode with reduced RFG rate. The predicted heat flux on the furnace walls of this boiler is higher than that of a commercial air-fired boiler and of a conventional oxy-fuel boiler, although not higher than that of oil-fired utility power boilers.